MORPHOLOGICAL CHANGES AND OXIDATIVE HOMEOSTASIS IN THE LIVER TISSUES DURING LONG CENTRAL DEPRIVATION OF LUTEINIZING HORMONE SYNTHESIS BY TRIPTORELIN - O.A. Polyvyana; V.I. Shepitko; Ye.V. Stetsuk; O.Ye. Akimov; O.S. Yakushko; O.V. Voloshyna (Проблеми екології та медицини)
In recent years, researchers have focused on the problem of the dependence of the functioning of various organs and systems on the level of androgens. The effect of long inhibition of testosterone synthesis by triptorelin on liver tissue is poorly understood. The aim of this research was to establish the microscopic organization of rat livers, production of nitric oxide and the intensity of oxidative stress in the rat livers during experimental central deprivation of luteinizing hormone synthesis by diphereline injection on the 270-360th day of the experiment. The experiments were carried out on 30 sexually mature male white rats of the Wistar line. Rats were divided into 2 groups: the control group (10) and the experimental group (20). Animals from the experimental group were subcutaneously injected triptorelin at a dose of 0.3 mg of the active substance/ per kg of body weight for 360 days, while the control group received an injection of saline. It was found that oxidative stress develops in hepatocytes, which is morphologically confirmed by karyopyknosis of the nuclei, oxyphilia of the cytoplasm with the appearance of a significant number of vacuoles in it. The vessels of the microcirculatory bed react with stasis. An increase in the production of superoxide radical anion in rat liver may be due to the absence of an inhibitory effect of testosterone on macrophages and liver mitochondria, which is accompanied by depletion of antioxidant enzymes and the development of oxidative stress. The intensity of biochemical markers of oxidative stress on the 360th day is lower than on the 270th day, which is due to an increase in the activity of antioxidant enzymes and a decrease in the production of reactive oxygen species.